Strategi Penghidupan Petani Padi Sawah Pasca Bencana Gempa Bumi (Studi Kasus di Desa Sarampad, Kecamatan Cugenang, Kabupaten Cianjur) - Purnama, Miftah Gurnita; Kusumo, Rani Andriani Budi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
The earthquake that struck Cianjur in 2022 caused damage, including to the rice farming sector. Farmers implemented various strategies to maintain their livelihoods in the vulnerable conditions after the earthquake and to obtain a better livelihood. This study aims to: 1) identify changes in the livelihood assets of rice farmer households after the earthquake and 2) identify the livelihood strategies of rice farmer households after the earthquake. The study was conducted in Sarampad Village, Cugenang District, Cianjur Regency. The research design used a qualitative approach with a case study technique. There were 34 informants in this study, consisting of 18 key informants and 16 supporting informants, who were determined using snowball sampling. Data analysis was conducted descriptively using NVivo software. The results showed that the earthquake caused changes in all five categories of livelihood assets. Changes in natural assets were indicated by the drying up of irrigation water and damage to rice fields in the form of cracks and increased soil porosity. Changes in physical assets were indicated by damage to houses and agricultural tools. Changes in financial assets were indicated by difficulties in accessing agricultural capital. Changes in social assets were indicated by the inactivity of farmer groups. Changes in human assets were indicated by difficulties in finding agricultural labor. The livelihood strategies implemented by farming households after the earthquake include replacing and adding commodities, improving rice fields, utilizing home gardens, adding businesses other than farming, adding trade and service businesses, and utilizing asset ownership. Optimal and equitable collaboration is needed in the process of restoring the conditions of farmers and their businesses after the earthquake.